Die fiskalische Komponente einer Politik des Debt Management - Karl-Heinrich Hansmeyer; Klaus Mackscheidt (Kredit und Kapital, 1970)
The Fiscal Component of a Policy of Debt Management A modern debt policy should serve the attainment of several objectives, the aim of minimizing interest being confronted with a bundle of objectives embracing, among other things, liquidity-policy, wealth policy and growth policy objectives. To elucidate the difficulties involved ın their realization, a policy is described which satisfies the objective of minimizing interest and substantially extends and refines the older fiscal approach. That approach interpreted the objective from the short-term standpoint, i. e. substitution of government securities to attain the currently lowest interest costs. Long-term analysis, on the other hand, must include market processes and market forecasts. It is shown that a phased strategy of adaption to and division of the market must be the consequence of such a policy. Only knowledge of the strategies serving to attain the objective of interest minimization reveals the conflicts of objectives which occur when conflicting, non-fiscal objectives are pursued to an increasing extent.
Keywords: 330